Implementation of Analytical Planning Systems - Moses, Michael A. (Management Science, 1975)
Decision makers in large organizations are faced with numerous alternative allocations of investment funds, financing possibilities and governmental and financial restrictions. Sophisticated strategic planning systems can enhance management's decision efficiency by assisting in the selection and implementation of optimal policies. This paper describes one such system with emphasis on the design concept and the planning procedure in its particular organizational setting. For demonstration purposes, the example of implementation experience in acquisition analysis is presented.